ENT 530: Dfreshtoyou / Muhammad Fikri Abd Manaf, Siti Mastura Mohd Nor and Jumailah Mohd Ali - Abd Manaf, Muhammad Fikri; Mohd Nor, Siti Mastura; Mohd Ali, Jumailah (2017)
Our mission is to deliver quality remedies to the population. These remedies contain all necessary vitamins, minerals, and amino acids. Vitamins are the basis for growth and movement, reachingthe harmony in one's physical and psychological state, as well as it is the basis for the well-being and good mood. Our goal is to become the first local company that offers the individual solutions in picking up the right amounts of vitamins, minerals, and amino acids to the residents of taking into account the regional peculiarities of nutrition. We can change the world for the better only with care for people.